PENGARUH PENGGUNAAN METODE SIMULASI TERHADAP KREATIVITAS BELAJAR PENDIDIKAN AGAMA KRISTEN SISWA KELAS VIII SMP NEGERI 2 TARUTUNG KABUPATEN TAPANULI UTARA TAHUN PEMBELAJARAN 2019/2020 - Simanullang, Putrisen (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2020)
The research aims to find out the positive and significant influence between simulation methods on the Christian Religious Education learning creativity of eighth grade Tarutung 2 Junior High School 2019/2020, the hypothesis that there  positive and significant influence between the use of simulation methods on student creativity of eighth grade Tarutung 2 Junior High School 2019/2020.The research used a descriptive quantitative inferential techniques, with population of all eighth grade students of Tarutung 2 Junior Hugh School with a total 194 people, with asample of 49 people.  The results of data analysis have positive and significant influence between simulation method and the Christian religious education learning creativity of eighth grade students of Tarutung 2 Junior High School in 2019/2020 learning year determination coefficient (r2) = 38.68% and a significant test of influence is obtained Fcount Ftable of  29, 37 4,05, Ho is rejected Ha accepted.Keywords: Simulation method, learning creativity